2013
DOI: 10.1136/bcr-2013-008893
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic haemiparesis

Abstract: SUMMARYHypoglycaemic haemiparesis (HH) is an uncommon but important presentation to the emergency department, and it often mimics stroke and is therefore frequently misdiagnosed by clinicians. The mechanism of haemiparesis is not fully understood. This case outlines a diabetic elderly woman, who had been having frequent hypoglycaemic episodes and presented to paramedics with hypoglycaemia associated with a right-sided haemiparesis. She was immediately transferred to the local stroke centre after presenting to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Numerous studies have reported that diabetes mellitus is closely related to the development of delirium. Kirresh et al 16 reported a case of hypoactive delirium induced by hypoglycemic hemiparesis, and Kotfis et al 17 reported that diabetes and elevated HbA1c levels are risk factors for delirium after cardiac surgery. Some systematic reviews and meta-analyses also revealed that the incidence of delirium is significantly increased in diabetic patients 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that diabetes mellitus is closely related to the development of delirium. Kirresh et al 16 reported a case of hypoactive delirium induced by hypoglycemic hemiparesis, and Kotfis et al 17 reported that diabetes and elevated HbA1c levels are risk factors for delirium after cardiac surgery. Some systematic reviews and meta-analyses also revealed that the incidence of delirium is significantly increased in diabetic patients 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, approximately 200 cases of hypoglycemia induced hemiparesis [10], of which 10 occurred with the use of sulfonylureas, have been published. [11][12][13][14][15][16][17][18][19][20]. One case of hemiparesis appeared with tolbutamide [11], four with glibenclamide [12][13][14], three with glyburide [16][17][18] and two with gliclazide treatment [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Only one case of tetraplegia after sulfonylureas was reported, however, in comparison to our case, neurological deficits disappeared after proper glucose level was restored. [11][12][13][14][15][16][17][18][19][20][21]. Only one case study described an incident of hypoglycemia imitating cerebellar AIS in a 55-year-old diabetic woman with sudden onset of unilateral cerebellar symptoms treated with glibenclamide [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation